Development of Inquiry Based Mathematics Learning Tools For Class IV Elementary Schools - Janewar, Janewar; Fauzan, Ahmad; Bentri, Alwen (International Journal for Educational and Vocational Studies, 2020)
Mathematical learning that is done does not achieve maximum learning outcomes. This is caused by their lack of learning activities, and the monotonous way of learning. The objectives of this study are to 1) produce inquiry-based mathematics lesson plans and worksheets for grade IV elementary schools with valid criteria, 2) produce inquiry-based mathematics worksheets and worksheets for class IV elementary schools with practical criteria, 3) produce inquiry-based mathematics worksheets and worksheets for inquiry Class IV Elementary School with effective criteria. This study is an educational research model design research that develops a product. This research procedure 1) preliminary analysis stage, 2) design phase, 3) assessment stage. Data collection instruments for interview guidelines, observation sheets. The data analysis stage uses practicality results and effectiveness test data. The results showed that 1) the results obtained illustrated that the developed Mathematics Worksheets were valid and could be used in learning Mathematics, 2) the practicality of inquiry-based Mathematics Worksheets provided that the Inquiry-based Mathematics Worksheets were very very practical to use and could increase student interest in Mathematics learning, 3) the effectiveness of using Inquiry-based Math LKS, student learning activities while learning to use LKS are very high and student learning outcomes in the cognitive, affective, and psychomotor domains also show good results. These observations provide an illustration that the use of Inquiry based Mathematics Worksheet has been effective.